2002
DOI: 10.3748/wjg.v8.i2.288
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study on TTV infection in hepatitis of unknown etiology

Abstract: To investigate the state of infection, replication site, pathogenicity and clinical significance of transfusion transmitted virus (TTV) in patients with hepatitis, especially in patients of unknown etiology. METHODS:Liver tissues taken from 136 cases of non-A non-G hepatitis were tested for TT virus antigen and nucleic acid by in situ hybridization (ISH) and nested-polymerase chain reaction (PCR). Among them, TT virus genome and its complemental strand were also detected in 24 cases of autopsy liver and extrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
(53 reference statements)
0
13
0
1
Order By: Relevance
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…Since the first isolation of TTV, most studies have shown that it might be relevant to liver disorders and liver damage and have a possible association with fulminant hepatitis, cryptogenic liver disease, non-A-G hepatitis, posttransfusion hepatitis, liver cirrhosis, and hepatocellular carcinoma (11,22,37,41,57,65). At the same time, epidemiological associations of TTV with B-cell lymphoma, Hodgkin's disease, aplastic anemia, idiopathic pulmonary fibrosis, acute respiratory disease, and autoimmune rheumatic disorders have also been described (6,16,29,30,32,52).…”
mentioning
confidence: 99%
“…Moreover, the liver cell infection is productive, finally resulting in degeneration of infected cells. These findings seem to suggest that the biochemical liver function abnormalities seen in some of the viraemic subjects [Lou et al, 1999;Dai et al, 2001;Hu et al, 2002;Desai et al, 2005] may be a direct result of cellular changes due to viral infection. They also imply that the virus (at least the genotype 1a), has the potential to cause direct cell damage in the liver in case of unrestricted viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it may be possible that release of virus in small doses in the extracellular matrix might result in sensitization of the host's immune response to the virus and may be responsible for the chronicity of the infection. Earlier, it has been indicated that TTV may act as a promoter of chronicity and deterioration of acute hepatitis and can affect liver cirrhosis and HCC in cases where the fibrosis is deeply advanced not as a genomic factor but through irregular regeneration [Sioda et al, 2001;Hu et al, 2002]. Altogether the TTV infection of the Chang liver cell line seems to be a valid model to study TTV infection of the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus has been detected in nearly all tissues of the body [22]. Several studies point towards its association with liver and renal diseases [23][24][25]. It has also been detected in various types of carcinoma including leukemia and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%